Dysregulated glucocorticoid-responsive immune genes in peripheral blood mononuclear cells as a shared molecular signature of autism spectrum disorder and irritable bowel syndrome - Kuo Zhang; Fangfang Mou; Jing Liu; Jianzhong Wang (PLoS ONE, 2026)
Background Autism spectrum disorder (ASD) is frequently accompanied by gastrointestinal (GI) disturbances resembling irritable bowel syndrome (IBS). While dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis and impaired glucocorticoid-responsive immune (GRI) signaling are proposed links between these disorders, the precise molecular mechanisms remain poorly understood. Methods We performed an integrative transcriptomic analysis of peripheral blood mononuclear cells (PBMCs) from ASD and IBS cohorts. Our approach combined single-sample Gene Set Enrichment Analysis (ssGSEA), differential expression profiling, weighted gene co-expression network analysis (WGCNA), and machine-learning-based feature selection. We utilized single-cell RNA sequencing to resolve cellular sources, while transcription factor, miRNA, and Connectivity Map (CMap) analyses identified regulatory mechanisms and potential drug candidates for reversing GRI-associated signatures. Results GRI-associated transcriptional activity was markedly elevated in the ASD group and moderately upregulated in the IBS group. Network and enrichment analyses revealed a convergence of immune recognition and cytokine signaling pathways. We identified four core genes—LRFN1 , NUAK2 , TMEM154 , and GAPT—that consistently discriminated disease status. These genes were primarily expressed in monocytes, natural killer (NK) cells, and B cells. Regulatory analysis implicated stress-responsive transcriptional control and extensive miRNA modulation in these processes. CMap analysis identified RN-486, saracatinib, and batimastat as compounds predicted to restore GRI homeostasis. Conclusions These findings define a shared GRI-associated molecular signature linking systemic stress adaptation to immune dysregulation along the brain–gut axis. This study provides novel mechanistic insights and identifies potential transcriptomic biomarkers and therapeutic targets addressing the shared molecular architecture between ASD and IBS.